Pembentukan Karakter Anak Dalam Mewujudkan Nilai Sosial Spiritual di Desa Cibuntu, Kabupaten Purwakarta - Rifqoh, Athifah; Suhendra, Suhendra; Sukmaguna, Aura Sekar; Dewi, Ineke Eka Chandra; Tharik, Jabal Al; Amani, Zata (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
This research was carried out in Cibuntu Village, Wanayasa District, Purwakarta Regency, to describe how children's character is formed in realizing social and spiritual values through social and spiritual programs found in the State Elementary School and Madrasah of Cibuntu Village. The method used in this research is qualitative research using data collection through interviews with elementary school and MDTA teachers, documentation, direct observation at elementary schools, and MDTA and literature studies. This research shows that there are indicators of social character, such as discipline, honesty, self-confidence, responsibility and cooperation. Meanwhile, spiritual character indicators include student behaviour related to social relationships, ethics, tolerance, sincerity, prayer and gratitude. Then, there are social and spiritual programs at SDN and MDTA, such as community service, social fundraising, picketing and religious activities. In implementing this program, there are supporting factors such as children's enthusiasm for learning and parental support. In contrast, the inhibiting factors are parental disapproval, long road access, inadequate facilities and a lack of human resources in schools